2016
DOI: 10.1016/j.blre.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures in B-cell lymphoma: How can these improve precision in diagnosis and inform prognosis?

Abstract: Current genomic technologies have immensely improved disease classification and prognostication of major subtypes of B-cell lymphomas. This novel genetic information has not only aided in diagnosis, but has also revealed a landscape of critical molecular events that determine the biological and clinical behavior of a lymphoma. In this review, we summarized the genetic characteristics of major subtypes of B-cell lymphomas, including diffuse large B cell lymphoma (DLBCL), follicular lymphoma (FL), Burkitt lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 130 publications
2
7
0
1
Order By: Relevance
“…For example, the frequency of TP53 mutations was comparable, reaching 22.8% in MCL and 19.8% in DLBCL. These results match well with the recently published comprehensive data presenting 25% for MCL and 20 % for DLBCL (7). Similarly, the ratio of missense TP53 mutations was comparable for MCL and DLBCL reaching 76.9 and 82.8%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, the frequency of TP53 mutations was comparable, reaching 22.8% in MCL and 19.8% in DLBCL. These results match well with the recently published comprehensive data presenting 25% for MCL and 20 % for DLBCL (7). Similarly, the ratio of missense TP53 mutations was comparable for MCL and DLBCL reaching 76.9 and 82.8%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the data have been reviewed and summarized for DLBCL, follicular lymphoma (FL), Burkitt lymphoma (BL), mantle cell lymphoma (MCL), marginal zone B-cell lymphoma (MZBL) and primary mediastinal B-cell lymphoma (PMBL). Acquisition of TP53 mutation was demonstrated as one of characteristic markers for DLBCL and MCL, reaching frequency 20 and 25%, respectively, but not for other lymphomas (7). This supports the concept of alternative ways abrogating the p53-dependent apoptosis.…”
Section: Complex Analysis Of the Tp53 Tumor Suppressor In Mantle Cellsupporting
confidence: 52%
“…CREBBP , KMT2D (previously termed MLL2 ), BCL2 , EZH2 , and TP53 ] and T‐lineage (e.g. TET2 , LRRK2 , PCLO , SPEN ) lymphomas, as seen in de novo diseases (Iqbal et al , , ). Consistent with this observation, mutation burden was higher in B‐cell versus T‐cell lymphomas.…”
Section: Resultsmentioning
confidence: 99%
“…definition, patients may develop accompanying B-cell lymphoproliferative disorders or clonal plasma cell proliferations as reported previously. 7,8 Importantly, recent studies have shown that AITL has a gene expression profile similar to that of follicular helper T (T FH ) cells, 2,9,10 a subset of T helper cells in the germinal center that promotes B-cell maturation and differentiation into plasma cells in cooperation with FDCs. Accordingly, in addition to expressing pan-T-cell antigens such as CD3 and CD5, the neoplastic cells of AITL usually express T FH markers such as CD10, BCL6, and/or PD-1.…”
mentioning
confidence: 99%